Analisa Kualitas Laba Dan Prediksi Kebangkrutan Perusahaan Dengan Metode Altman Z–Score (Studi Kasus Pada Perusahaan Yang Terdaftar Dalam Indeks Lq-45 Periode Laporan Keuangan Tahun 2013 - 2017) - Riri Suliani (Universitas Tarumanagara, 2019)
The aim of this research was to analyze the earning quality and corporate bankruptcy prediction by using Altman Z-Score method, and analyze the influence of the earnings quality against the bankruptcy prediction results. The sample data are 45 companies listed in the index of LQ-45 for the period February 2013 until August 2017 with purposive sampling method. The test results showed that earning quality has a greater relationship influence on a the prediction of corporate bankruptcy for bankrupt categories 37.66% than in the prediction of corporate bankruptcy for non bankrupt categories (health) only 8.61%.